2019
DOI: 10.1016/j.celrep.2019.11.090
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-Specific Lipid Hydrolysis Prolongs Lifespan through Global Lipidomic Remodeling

Abstract: Highlights d Muscle-specific lipid catabolism extends lifespan in a noncell-autonomous manner d Depletion of IMLDs via the PKA/ATGL pathway remodels the global lipidome d Muscle-specific PLA 2 generates ''lipokines'' that signal to tissues outside of the muscle d Regulators of metabolic homeostasis in neurons are required to promote longevity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 92 publications
0
19
0
Order By: Relevance
“…However, the Δ9 desaturase double mutant strains carrying a mutation in fat-7 , fat-7; fat-5 and fat-6; fat-7 , did not exhibit an OA-induced increase in brood size ( Figure 4A ). These results suggest that OA is not required for decreased fecundity but may rather be a limiting factor for reproduction after passage through the starvation-induced dauer stage, whether for nutrition or as a signaling molecule across tissues to regulate physiology ( Schmeisser et al, 2019 ; Starich et al, 2020 ). These results also indicate that fat-7 is required for the OA-induced increase in brood size, which was unexpected given that it acts upstream of OA in fatty acid synthesis and suggests that FAT-7 has additional roles in fatty acid metabolism ( Figure 3—figure supplement 1B ; Watts, 2009 ).…”
Section: Resultsmentioning
confidence: 95%
“…However, the Δ9 desaturase double mutant strains carrying a mutation in fat-7 , fat-7; fat-5 and fat-6; fat-7 , did not exhibit an OA-induced increase in brood size ( Figure 4A ). These results suggest that OA is not required for decreased fecundity but may rather be a limiting factor for reproduction after passage through the starvation-induced dauer stage, whether for nutrition or as a signaling molecule across tissues to regulate physiology ( Schmeisser et al, 2019 ; Starich et al, 2020 ). These results also indicate that fat-7 is required for the OA-induced increase in brood size, which was unexpected given that it acts upstream of OA in fatty acid synthesis and suggests that FAT-7 has additional roles in fatty acid metabolism ( Figure 3—figure supplement 1B ; Watts, 2009 ).…”
Section: Resultsmentioning
confidence: 95%
“…Extensive research has focused on the contributions of fatty acid oxidation to lipid metabolism and cell fate decisions but there has been a paucity of research on the role of nonoxidative lipid pathways in regulating lymphoid cell fate (Lee et al, 2018;Pernes et al, 2019). While the role of lipidome remodeling in T lymphocyte fate has not yet been evaluated, recent studies have highlighted the importance of the cell's lipidome in mesenchymal stem cell differentiation (Levental et al, 2017), myelopoiesis (Mitroulis et al, 2018), stem cell pluripotency (Wu et al, 2019), and lifespan (Schmeisser et al, 2019). Our study showed that during CD4 T cell differentiation, glucose provides carbons for fatty acid synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the lipid metabolism research in immune cells has focused on the incorporation of PUFAs into the membrane, with the ratio of n-3 to n-6 PUFAs found to modulate inflammation and autoimmunity (Kim et al, 2018;Monk et al, 2012;Shaikh and Edidin, 2006). While the role of lipidome remodelling in T lymphocyte fate has not yet been evaluated, recent studies have highlighted the importance of the cell's lipidome in mesenchymal stem cell differentiation (Levental et al, 2017), myelopoiesis (Mitroulis et al, 2018), stem cell pluripotency (Wu et al, 2019), as well as extended lifespan (Schmeisser et al, 2019). In the study presented here, we find that the aKG-mediated attenuation of Treg polarization is coupled to a robust lipidomic remodelling.…”
Section: Discussionmentioning
confidence: 99%